Analysis of some error-causing factors in two-dimensional geoelectrical studies and providing a solution to minimize them - Hosein Moghaddasi; Mohsen Moghaddasi; Ahmad Neyamadpour (Journal of Economic Geology)
In recent years, two-dimensional geoelectrical surveys have become one of the common and conventional methods in mineral exploration, groundwater resources investigations, engineering geophysics, archeology, etc. However, in some cases, these studies could not reach the targeted and expected results, and sometimes the geophysical results obtained have had a significant distance from the results obtained from direct studies such as drilling, etc. In this article, authors try to comprehensively analyze some factors that cause errors in two-dimensional geoelectrical studies, and on the other hand, state solution for minimizing the amount and severity of the discussed errors. Also, it has been tried to provide practical solution and approach for minimizing the error factors by a deep understanding of the source and mechanism of error factors. Finally, a case study in which geoelectrical data has been acquired by applying that new approach has been presented.